Root-Induced Iron Oxidation, pH Changes and Zinc Solubilization in the Rhizosphere of Lowland Rice - Kirk, G.J.D.; BAJITA, J.B. (Wiley, 1995)
Rice plants (Oryza sathiva L., cv. IR34) were grown with their roots sandwiched between cylinders of an anaerobic low‐Zn Mollisol. After periods of root‐soil contact of up to 12 d (total plant age c. 28 d) the profiles of different Zn fractions, reduced and oxidized Fe, and pH in the soil near the root plane' were determined. The concentration of easily plant‐extractable Zn in the soil (measured by extraction in I M KCl) was negligible, and so it was necessary for the plants to induce changes in the soil to solubilize Zn. After 6 d, there was a substantial accumulation of Zn associated with organic matter and amorphous ferric hydroxide within 4–5 mm of the root plane. Over the next 6 d, the accumulation continued but there was a substantial depletion of the accumulated fractions within 2 mm of the root plane. The zones of accumulation and depletion coincided with zones of Fe(III) accumulation and soil acidification in which the pH decreased from the bulk soil value of 7.3 by over 0.2 pH units; i.e. a two‐fold increase in H+ concentration, The acidification was the result of H+ released from the roots to balance excess intake of cations over anions, and H+ generated in the oxidation of Fe(H) by root‐released O2. At the high pH and CO., pressure of the experimental soil (7.3 and c. 0.9 kPa. respectively), soil acidity diffusion is fast and consequently the pH drop at the root surface was small. The rate of Fe oxidation peaked before 6 d, but the acidification and Zn accumulation continued beyond 6 d unabated. It is concluded that Fe oxidation released Zn from highly insoluble fractions, and that this Zn was re‐adsorbed on Fe(OH)3 and on organic matter in forms that were acid‐soluble and therefore accessible to the plants.